Carotenoids modulate stress tolerance and immune responses in aquatic animals - Keng, Chin Lim; Md. Yusoff, Fatimah; Karim, Murni; Natrah, Fatin M. I. (John Wiley and Sons, 2023)
Aquaculture continues to expand swiftly and remains the fastest-growing food industry worldwide amidst ever-present threats from chronic stressors and emerging diseases. Nutrition plays a pivotal role in the profitability and viability of the aquaculture industry that steered a paradigm shift to therapeutic nutrition. Carotenoids, also termed tetraterpenoids, have garnered considerable attention owing to their therapeutic attributes and immeasurable health benefits, which incited a surge in global demand. These biological pigments are recognized to promote immune systems and antioxidant defence mechanisms in both aquatic vertebrates and invertebrates. This review brings forth existing scientific evidence and underscores the notable roles of carotenoids as biologically active constituents with anti-stress and immunostimulatory potentials in farmed aquatic animals whilst explicating possible mechanisms of action. Empirical data unequivocally established the modulatory functions of carotenoids on endogenous antioxidant enzymes, innate and adaptive arms of the immune response, as well as the expression of multiple antioxidant and immune-related genes. The comprehensive information presented is beneficial to deepen our understanding of the utilization of carotenoids as potent stress alleviators and immunostimulants in cultured aquatic animals, which is translated into improved health. Advancements in aquatic animal health and welfare could principally contribute to reconstructing a more sustainable aquaculture industry. This article may be useful for subsequent investigations towards further advances in research and innovation to a greener blue revolution in solving the challenge of global food security.